Cost of care associated with utilization of telehealth in clinical trials - Emily Gleason; Leslie Andriani; Elizabeth A. Tubridy; Destiny Uwawuike; Simon Gunter; Nathanael C. Koelper; Heidi S. Harvie; Emily M. Ko (Gynecologic Oncology Reports)
Objective: Due to COVID-19 pandemic restrictions, telehealth was incorporated into standard oncologic care and clinical trial operations. We sought to analyze whether telehealth changed cost of care compared to traditional clinical trial operations. Methods: We conducted a retrospective cohort study of gynecologic oncology patients enrolled in therapeutic clinical trials at a National Cancer Institute designated center, comparing the cost of cancer care on trial pre-TELEhealth (9/30/2019 to 3/15/2020) versus during TELEhealth (3/16/2020 to 8/20/2020). Inclusion required trial participation during both study periods, ≥1 telehealth visit, and identifiable billing records. The analysis was from a healthcare sector perspective. Cost per patient per month on trial was calculated for scheduled (per protocol) and unscheduled (non-protocol) encounters using 2020 national Medicare reimbursement rates, not institution-specific prices. Pairwise t-tests between pre-TELE and TELE periods were performed. Results: Twenty-eight patients were included in the study. The majority of patients (93 %) had ovarian cancer. One patient (4 %) had uterine and 1 (4 %) had concurrent ovarian/uterine cancer. Most patients had advanced-stage disease at diagnosis (93 %). Mean cost per patient per month was similar in pre-TELE and TELE periods ($3797 vs. $4720, p = 0.064). There were no cost differences among scheduled or unscheduled encounters, office or ED visits, admissions, outpatient procedures, nor those billed to study sponsors or patient’s insurer. Conclusions: Incorporating telehealth in gynecologic cancer clinical trials during the COVID-19 pandemic did not increase cost of care and may be a mechanism for decentralizing clinical trials, reducing barriers to trial participation, and improving the value of cancer care.